Equilibrium partial pressure of CO2 in Callovian–Oxfordian argillite as a function of relative humidity: Experiments and modelling. (1st August 2016) - Lassin, Arnault; Marty, Nicolas C.M.; Gailhanou, Hélène; Henry, Benoît; Trémosa, Joachim; Lerouge, Catherine; Madé, Benoît; Altmann, Scott; Gaucher, Eric C.
Abstract: Having previously demonstrated that the mineral assemblage of claystone can impose its pCO2 under saturated conditions, we here study the effect of rock desaturation, i.e. the evaporation of pore water, on the partial pressure of CO2 (pCO2 ) in Callovian–Oxfordian argillite from the Paris Basin (France). In this new study, which combines experiments at room temperature and geochemical modelling, we examine the primary role of capillary forces on chemical equilibria for relative humidity values ranging between 50% and 100%. In particular we are able, without any fitting parameters, to model the experimental decrease of pCO2 as a function of decreasing water content in the argillite. This application to a complex natural system not only confirms the theoretical concepts of geochemistry in capillary contexts, but is promising with respect to other systems, both natural (soil, rock) and industrial (ceramics, granular material).